Synthesis of MgFe2O4/Reduced Graphene Oxide Composite and Its Visible-Light Photocatalytic Performance for Organic Pollution - Fengmin Wu; Wenlu Duan; Mei Li; Hang Xu (International Journal of Photoenergy)
Recently, binary metal oxides have been proven to be the most investigated semiconductors due to their high activity for the removal of organic pollutants. In this paper, to improve the photocatalytic efficiency of MgFe2O4, a MgFe2O4/reduced graphene oxide (MFO/rGO) photocatalyst was synthesized by a facile generalized solvothermal method. The morphology, structure, and photocatalytic activities in the degradation of methyl orange (MO) reaction were systematically characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, and UV-vis absorption spectroscopy, respectively. The results showed that the MFO/rGO composite exhibited enhanced photocatalytic performance in the photodegradation of MO under visible-light irradiation and reached a maximum degradation rate of 99% within 60 min of irradiation. This excellent photocatalytic performance is attributed to the introduction of rGO in the composite, which can effectively reduce the photoproduction of the electron-hole pair recombination rate. The excellent photocatalytic activity reveals that the MFO/rGO composite photocatalyst is a promising photocatalyst with good visible-light response and has potential applications in the field of water treatment.